The Penguatan Kesehatan Mental Sosial-Emosional Anak Usia Dini di Era Digital - Ikha Durrotun Nasikhah; Nihna Atho’a Rosfalia; Wiwin Dwi Kusuma (UAS PRESS, 2026)
The development of digital technology has a significant impact on the lives of young children, including aspects of socio-emotional mental health. Uncontrolled exposure to digital media can affect children's ability to manage emotions, interact with peers, and build healthy social relationships. Therefore, it is necessary to provide guidance involving the roles of teachers and parents so that the use of technology can be directed positively. This community service activity aims to strengthen the social-emotional mental health of early childhood children thru a program that guides the wiser use of digital technology. The method used in this activity is Participatory Action Research (PAR), which is carried out participatively thru several stages, namely problem identification, program planning, activity implementation, reflection, and joint evaluation. The community service activity is conducted at TK Darul Mukhlasin Puger Jember, involving teachers, parents, and children as the main targets of the program. Data collection techniques were carried out thru observation, interviews, documentation, and measurement of children's social-emotional abilities before and after the program was implemented. The results of the activities show an improvement in several indicators of children's socio-emotional development, such as the ability to manage emotions, empathy toward friends, positive social interactions, and children's involvement in learning activities. In addition, this program also enhances the understanding of teachers and parents regarding the importance of balanced guidance in the use of digital technology. These findings indicate that collaboration between schools and families is an important factor in supporting the socio-emotional mental health of children in the digital era. This service program is expected to become one of the model approaches that can be applied in efforts to support the holistic development of early childhood.